ADHD and the Early Career Teaching Librarian: An Autoethnography - Swick-Jemison, Jocelyn (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2023)
What draws the ADHD brain to a job like librarianship? I was diagnosed with ADHD at the age of 42, five years into my career as a teaching librarian at a large public university. As I talked to colleagues and interacted with fellow librarians online, I noticed a trend of librarians being open and honest about their neurodivergence. As a result, this autoethnography explores my personal experience as a teaching librarian with ADHD. I will outline how ADHD affects my role in the following areas: being part of a team, leading a classroom, collaborating with faculty, and managing planning, grading, and communications. I explore these themes through six common ADHD traits: idealism, being an empath, rejection sensitivity dysphoria, being scatter brained, imposter syndrome, and hyperfocus. I will explore how these traits affect me daily, as well as how they have affected my career trajectory.